Beyond the 1984 Perspective: Narrow Focus on Modern Wildfire Trends Underestimates Future Risks to Water Security - Murphy, Brendan P.; Yocom, Larissa L.; Belmont, Patrick (Earth's future, 2018)
The western United States remains well below historical wildfire activity, yet misconceptions abound in the public and news media that the area burning by wildfire each year in the American West is unprecedented. We submit that short‐term records of wildfire and a disproportionate focus on recent fire trends within high‐profile science stoke these misconceptions. Furthermore, we highlight serious risks to long‐term water security (encompassing water supply, storage, and quality) that have only recently been recognized and are underestimated as the result of skewed perspectives of wildfire. Compiling several data sets, we illustrate a comprehensive history of western wildfire, demonstrate that the majority of western settlement occurred during an artificially and anomalously low period of wildfire in the twentieth century, and discuss the troubling implications the misalignment of wildfire activity and human development may have for the long‐term projections of water security. A crucial first step toward realigning public perspectives will require scientists and journalists to present recent increases in wildfire area within the context and scale of longer‐term trends. Second, proper housing development and resource management will require an appreciation for the differing western ecosystems and the flexibility to adopt varied approaches. These actions are critical for realigning public understanding of both the direct and indirect risks associated with wildfire and ensuring adequate and appropriate measures are taken as we navigate a future of increasing fire in the West. Plain Language Summary Area burning by wildfire each year in the western United States has increased rapidly over the past three decades, and news media frequently assert that recent extents of wildfire are record breaking. However, research shows that area burning in recent years is a small fraction of what burned prior to the 1920s. Why does this misconception persist and why does it matter? We document that high‐profile science articles, frequently cited by the media, disproportionately use data sets that only extend back to 1984. This short‐term perspective promotes the false impression that burned areas today are unprecedented. Moreover, this misconception results in the underestimation of serious risks that wildfires pose to long‐term water security. High‐severity wildfires cause excessive erosion, and with wildfire activity increasing, due to buildup of fuels and increased aridity in the western United States, substantially more sediment can be expected to degrade water quality and reduce water storage capacity in reservoirs throughout the West. Solutions are complex and varied, but despite the known risks, we advocate for allowing more managed (low‐severity) wildfire to burn under appropriate conditions, in an effort to reduce potential for high‐severity burns and associated erosion, thereby extending the lifespan of reservoirs. Key Points Disproportionate scientific focus on recent wildfire trends leads to public misconceptions about wildfire potential in the western United States Misconceptions about wildfire underlie a lack of recognition of serious indirect risks wildfires pose to water security The scientific community must realign public perspectives and emphasize diverse actions in ecosystem, fire, and water management